2012
DOI: 10.5402/2012/674523
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics and Survival Studies of Rhabdomyosarcoma in East Egypt: A Five-Year Multicenter Study

Abstract: Background. Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children, it represents 5–8% of childhood malignancies. Aim of the Work. To evaluate the epidemiological characteristics and treatment outcome in two pediatric oncology centers. Patients and Method. A retrospective analysis was performed on 41 medical records of children with RMS during 6 years period. Results. The median age of patients was 6 years with 80.4% below 10 years. Head and neck was the most common primary site. Embryonal R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
4
10
2
Order By: Relevance
“…This result was closely comparable to an an Egyptian Multicenter study which was conducted over a 5 -year period between 2004 and 2009 , and showed that the median age of patients was 6 years with 80.4% below 10 years . (19) This is similar to a recent study done in the central region of Tunisia by Missaoui N et al in 2010 who reported that almost two third of patients with RMS were diagnosed before 7 years of age. (20) This also agrees with data from the IRS IV which reported that the median age of patients with RMS was 5-year, with 72% of patients below the age of 10 years.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This result was closely comparable to an an Egyptian Multicenter study which was conducted over a 5 -year period between 2004 and 2009 , and showed that the median age of patients was 6 years with 80.4% below 10 years . (19) This is similar to a recent study done in the central region of Tunisia by Missaoui N et al in 2010 who reported that almost two third of patients with RMS were diagnosed before 7 years of age. (20) This also agrees with data from the IRS IV which reported that the median age of patients with RMS was 5-year, with 72% of patients below the age of 10 years.…”
Section: Discussionsupporting
confidence: 90%
“…(3,20,23 (23) This is supported by a five-year study from East Egypt conducted between 2004 and 2009, which showed that the embryonal RMS was the most commont histopathologic subtype (61.9%), followed by alveolar (28.6%) and lastly the botryoid and spindle subtypes in 4.7% for each. (19) This is not similar to a study conducted in the Japan by Suita S, et al in 2005 ,who reported that the alveolar type accounted for 36. 8% of RMS cases, while 35.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…RMS in children can originate from any site of body. Some researchers have showed that the head and neck region is the most common primary site in children with RMS, which accounts for 45%, while the primary site in the orbit accounts for 25-35% of patients with RMS in the head and neck region (Turner and Richmon, 2011;Badr et al, 2012;Salman et al, 2012). In this study, the most frequent positions in patients with RMS were in the orbit and eyelid, which accounted for 56.09% (23/41).…”
Section: Discussionmentioning
confidence: 71%
“…As many other researchers have reported, better outcome was observed in the younger patient group (<18 years old), only one of whom died during the 5 years of follow-up. In contrast, of the older patients (>18 years old), 10/15 died in the same period (Hosoi et al, 2007;Sultan et al, 2009;Badr et al, 2012). The most likely reason for this is the fact that among younger patients, embryonal RMS was the most common diagnosis (80%), while this histological type was not found in the older patient group (0.001).…”
Section: Discussionmentioning
confidence: 98%